Predominant Catalase-negative Soil Bacteria. III. Agromyces, gen. n., Microorganisms Intermediary to Actinomyces and Nocardia - Gledhill, William E. (1969)
The occurrence of filamentous, branching, catalase-negative bacteria as a numerically predominant microflora of various soils was demonstrated by using a dilution frequency isolation procedure. The major characteristics of these organisms were those of the order Actinomycetales. However, they could not be placed in any of the present genera of this order and, therefore, a new genus, Agromyces, was proposed for these organisms. This genus includes catalase-negative, nutritionally-fastidious microorganisms whose cells produce a true branching mycelium that fragments into coccoid and diphtheroid forms. Also, they have an oxidative metabolism, are microaerophilic to aerobic, and contain neither diaminopimelic acid nor lysine as major constituents of the cell wall glycopeptide. The type species would be Agromyces ramosus, gen. n., sp. n. The possible importance of these organisms in clarifying certain phylogenetic relationships of the Actinomycetales is discussed.